2005
DOI: 10.5751/es-01307-100125
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Sprawl on Biodiversity: the Ant Fauna of the Lower Florida Keys

Abstract: ABSTRACT. Sprawling development can affect species composition by increasing the rate of invasion by non-native species, and decreasing the persistence of native species. This paper briefly reviews the scientific literature on the impacts of sprawl on biological diversity, with specific emphasis on the influence of sprawl on non-native species richness. We then explore the relationship between sprawl and biodiversity using a data set of ant species collected from 46 habitat patches located in the increasingly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Two of the most comprehensive field studies completed to date demonstrate significant effects of subdividing private ranches on bird, carnivore, and plant communities in Colorado (Odell and Knight, 2001;Maestas et al, 2001). On the other hand, differences in the presence of native ant species were not detected in southern Florida, despite marked increases in exotic ants found at exurban sites (Forys and Allen, 2005). The same was true for ants and small mammals in the Sierra Nevada, California (Manley et al, 2006), although the lack of detectable effect could represent an extinction debt that will lead to the loss of native species over time (Tilman et al, 2002).…”
Section: Introductionmentioning
confidence: 92%
“…Two of the most comprehensive field studies completed to date demonstrate significant effects of subdividing private ranches on bird, carnivore, and plant communities in Colorado (Odell and Knight, 2001;Maestas et al, 2001). On the other hand, differences in the presence of native ant species were not detected in southern Florida, despite marked increases in exotic ants found at exurban sites (Forys and Allen, 2005). The same was true for ants and small mammals in the Sierra Nevada, California (Manley et al, 2006), although the lack of detectable effect could represent an extinction debt that will lead to the loss of native species over time (Tilman et al, 2002).…”
Section: Introductionmentioning
confidence: 92%
“…Most studies on ants have focused on fragments of natural habitats in urban environments and the differences in species richness across urban to rural gradients, with often inconsistent patterns between cities (McKinney 2008;McIntyre 2009). For example, a number of studies of ants have shown decreases in species richness in urban environments (Pisarski and Czechowski 1978;Suarez et al 1998;Malozemova and Malozemov 1999;Yamaguchi 2004;Lessard and Buddle 2005;Pacheco and Vasconcelos 2007;Thompson and McLachlan 2007;Clarke et al 2008) though others have shown little to no difference (Carpintero et al 2003;Gibb and Hochuli 2003;Forys and Allen 2005;Vepsäläinen et al 2008).…”
Section: Introductionmentioning
confidence: 96%
“…Blair () identified different effects of urban sprawl on birds at multiple levels of organization, detecting that species richness and diversity peaks at intermediate levels of urbanization. Forys and Allen (Forys & Allen, ) found that neither native nor rare ant species were significantly affected by urban sprawl, whereas exotic species richness was positively correlated with the amount of development. Concepción et al () found important impacts of urban sprawl on species richness of plants and birds, which varied considerably depending on the species groups, urban sprawl components and spatial scales considered.…”
Section: Introductionmentioning
confidence: 99%